"His Game is Called Survivin": A Resistance to Resilience. Issue 2 (August 2020) - Baker, Natalie D.
The discipline of disaster studies has been hesitant to critically interrogate dual discourses of vulnerability and "building resilience" in a meaningful way as it continues to dominate research and practice. This is despite deep engagement within different disciplines to offer radical reconsiderations of these discourses. I use multi-year long autoethnographic immersion into the problematic of resilience. I integrate personal experience as a White, female scholar who studies disasters, with an almost decade-long project focused on the pre-and-post Katrina context of New Orleans bounce rap. I task what it means "to be resilient" and who decides when groups have reached this state. I situate an empirical challenge to metanarratives of resilience and the colonialism they suggest, and also task resilience as constructed by elites and imposed on those decided as vulnerable. This work suggests a dramatic shift away from the building resilience discourse into meaningful engagement with the institutional neglect of the colonial present that fosters disaster in the first place.